Investigations on Veterinary Folklore in the Lower Euphrates Basin: Folk Beliefs and Practices Applied on Animals - Yüksel, Erhan; Özen, Rahşan (My University, 2021)
This study was aimed at the compilation and introduction to the scientific literature of the folk beliefs on animalsin the lower Euphrates basin, a major settlement area of common history, which has been home to severalcivilizations, and thus, is an area of great significance for folklore. For this purpose, in total 78 persons, residingin the lower Euphrates basin in the Adıyaman, Elazığ, Malatya and ?anlıurfa provinces and the Nizip district ofGaziantep province were interviewed in person. The findings obtained were assessed using the “content analysis”method. The study revealed that, in the lower Euphrates basin, some animals are considered to bring good luck;some animals are considered to bring bad luck. On the other hand, the findings obtained demonstrated that thedog, owl, and fox are considered to bring good luck and to bring bad luck. Furthermore, it was determined thatthe placenta of newly parturited animals is either hung on the branch of a fig tree or thrown into the river, in thebelief that this would increase the milk yield of lactating animals, and it was settled that “pox bowl” is used againstsmallpox, mole is used against “mole head” disease, and it was ascertained that the skull of horses, cattle, sheepand goats as well as tortoise shells are hung on the walls of houses and stables, in the belief that this wouldprotect the people and animals from the evil eye. In conclusion, rich folkloric elements related to folk beliefs onanimals were observed in the lower Euphrates basin and the beliefs of this region were found to be similar tothose maintained in the different regions of Anatolia.
Keywords: Folklor; Veterinerlik